Energy, Nitrogen, and Phosphorus Balances in Grazing Cattle Fattening Systems - Miguel Moreno Nápoles; Guillermo E Guevara Viera; Zoe Acosta Gutiérrez; Jorge Alberto Estévez Alfayate; Ángel E Ceró Rizo; Johny Carmilema Asmal; Clelia K Guzmán Espinosa; Servando A Soto Senra; Carlos S Torres Inga; Raúl V Guevara Viera (Revista de Producción Animal, 2019)
The aim of this work was to check the balance of energy, nitrogen, and phosphorus in pre-fattening and fattening bovine systems at Turiguanó Livestock Breeding Company, in the province of Ciego de Ávila, Cuba. The botanical composition of the farms evaluated was determined, and the energy, nitrogen, and phosphorus balances checked. The annual energy, nitrogen, and phosphorus balances were negative on the experimental farms. New strategies are required to enhance energy and nutrients (nitrogen and phosphorus) use, and increase beef production during the final stage. Therefore, improvements in recycling, balance, and efficiency in the use of energy and these minerals are linked to increases in live weight/day, and better final weights during that stage.